How do you simplify sqrt(x-1) + sqrt( 2x) = 3?

1 Answer
May 6, 2018

rarrx=2

Explanation:

rarrsqrt(x-1)+sqrt(2x)=3

rarrsqrt(x-1)=3-sqrt(2x)

rarr[sqrt(x-1)]^2=[3-sqrt(2x)]^2

rarrx-1=9-6sqrt(2x)+2x

rarr6sqrt(2x)=x+10

rarr[6sqrt(2x)]^2=[x+10]^2

rarr36*(2x)=x^2+20x+100

rarrx^2-52x+100=0

rarrx^2-2*x*26+26^2-26^2+100=0

rarr(x-26)^2=26^2-100=576

rarrx-26=sqrt(576)=+-24

rarrx=26+24,26-24=50 or 2

Putting x=50 in given equation, we get,

rarrsqrt(50-1)+sqrt(2*50)=17(rejected)

Putting x=2 in given equation, we get,

rarrsqrt(2-1)+sqrt(2*2)=3(accepted)

So, the required value of x is 2.